A review of salty waste stream management in the Australian dairy industry. (15th October 2018) - Chen, G.Q.; Talebi, S.; Gras, S.L.; Weeks, M.; Kentish, S.E.
Abstract: Saline wastewater is a by-product of cheese manufacturing and whey processing that can have serious environmental and economic consequences. Salty streams originating from dairy processing operations include chromatography wastes, clean-in-place wastewater, acid whey, salty whey and waste generated from whey demineralization processes such as nanofiltration, electrodialysis and ion exchange. With the participation of the major dairy companies in Australia, an industry wide survey was conducted to acquire a comprehensive understanding of the management strategies for these salty waste streams. High salinity waste streams are commonly directed to evaporation ponds. However, environmental impacts from land degradation, odour and dust have prevented the construction of further evaporation ponds in some areas of Australia. The survey results also show that disposal to municipal trade waste is not always effective, as the current levels of some salinity-related parameters are significantly higher than the levels allowed by the local water/environmental authorities. For high salinity streams, salt removal can lead to more substantial savings in trade waste charges compared to wastewater volume reduction. Thus, salt removal and recovery from salty waste streams has become a major focus of the sustainability agenda of the Australian dairy industry. Highlights: Industry wide survey of saline management practices in Australian dairy. Saline waste is generated from a number of processing operations. Both brine ponds and trade waste options for brine becoming more difficult. Salt removal from effluent is effective in reducing trade waste charges.